2022
DOI: 10.3390/nu14050957
|View full text |Cite
|
Sign up to set email alerts
|

Chicory: Understanding the Effects and Effectors of This Functional Food

Abstract: Industrial chicory has been the subject of numerous studies, most of which provide clinical observations on its health effects. Whether it is the roasted root, the flour obtained from the roots or the different classes of molecules that enter into the composition of this plant, understanding the molecular mechanisms of action on the human organism remains incomplete. In this study, we were interested in three molecules or classes of molecules present in chicory root: fructose, chlorogenic acids, and sesquiterp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 112 publications
(123 reference statements)
1
12
0
Order By: Relevance
“…For the cytotoxicity test, we utilized a mix of human cell lines composed of 80% of human colon adenocarcinoma Caco2 and 20% of HT-29. The preparation of the mix of human cell culture was realized according to Pouille et al [23]. The mix of Caco2 cell and HT-29 line were cultured in Dulbecco's Modi ed Eagle Medium (DMEM, Gibco, Thermo Fisher Scienti c), supplemented with 10% (v/v) of heat-inactivated fetal bovine serum (FBS) (Biowest, Nuaillé, France), 100 units/mL penicillin, 100 µg/mL streptomycin (Gibco, Life Technologies, Grand Island, NY, USA) and 10 mM nonessential amino acids (Gibco, Life Technologies, Paisley, UK).…”
Section: Hemolysis and Antibiotic Susceptibilitymentioning
confidence: 99%
See 1 more Smart Citation
“…For the cytotoxicity test, we utilized a mix of human cell lines composed of 80% of human colon adenocarcinoma Caco2 and 20% of HT-29. The preparation of the mix of human cell culture was realized according to Pouille et al [23]. The mix of Caco2 cell and HT-29 line were cultured in Dulbecco's Modi ed Eagle Medium (DMEM, Gibco, Thermo Fisher Scienti c), supplemented with 10% (v/v) of heat-inactivated fetal bovine serum (FBS) (Biowest, Nuaillé, France), 100 units/mL penicillin, 100 µg/mL streptomycin (Gibco, Life Technologies, Grand Island, NY, USA) and 10 mM nonessential amino acids (Gibco, Life Technologies, Paisley, UK).…”
Section: Hemolysis and Antibiotic Susceptibilitymentioning
confidence: 99%
“…To investigate the in ammatory and anti-in ammatory effects of Weissella strains, we used the promonocytic human cell line U937 according to the protocol described by Pouille et al [23]. The cell line U937 was cultured in Roswell Park Memorial Institute 1640 Medium (RPMI, Gibco, Thermo Fisher Scienti c) supplemented with 10% fetal bovine serum (FBS), 100 U/mL penicillin, 100 µg/mL streptomycin, and 2 mM glutamine in a humidi ed 5% CO 2 atmosphere at 37°C.…”
Section: In Ammatory Effects Of Weissella Strainsmentioning
confidence: 99%
“…Chicory is currently an important part of the human diet as a substitute for coffee and also as a major source of inulin, as well as use as a vegetable with its cultivated types, such as Brussels chicory, radicchio, and puntarelle [ 11 ]. Modern experimental studies have shown that chicory possesses a variety of pharmaceutical properties, ranging from antiulcerogenic, diuretic, analgesic, and wound-healing effects to an anti-metabolic disease potential (e.g., anti-diabetes, lowering blood pressure, and immunomodulatory effect) [ 9 , 11 , 12 ]. Moreover, our groups found that, in spite of no change in advanced atherosclerotic plaque size at the site of the brachiocephalic artery, Brussels chicory did elicit a “clinically favorable” stable-plaque phenotype with a reduction in necrotic size and an increase in collagen content and also the thickness of thin fibrous cap in Apoe −/− mice [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, chicory root contains other phytochemicals that are collectively known to have antioxidant, anticancer and anti-inflammatory properties [16]. These bioactive substances include coumarins, flavonoids, tannins, alkaloids, vitamins, minerals and essential oils [16].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, chicory root contains other phytochemicals that are collectively known to have antioxidant, anticancer and anti-inflammatory properties [16]. These bioactive substances include coumarins, flavonoids, tannins, alkaloids, vitamins, minerals and essential oils [16]. One of our recent studies also demonstrated that the inclusion of chicory in a cereal-based diet could significantly influence kidney and liver mineral contents and antioxidant capacity in nursery pigs [17].…”
Section: Introductionmentioning
confidence: 99%